(3hUjI Ydi Hf CHj WGdH dGHfg GdMSjf QVj Gddg YfgeG hCTjGA CNQis - (3CHhGdMSf Ydj Hf CHj WGdH Hf YHO GdeWdH,J (B40 (3g` s ((3YeQ GdeYQha HoeMGSH CQV Qhej s)
(3ChdgG (B:s
(3ChUi CejQ GdeDefjf Ydi hdOg GdMSjf YdjgeG GdSdGe abGd jGHfj ChUjc HJbhi Gddg s
(3BNQgG (B:s
(3hUd Ydjg eG OYGc hfGLGc CNjGQ HHGHc oQcY JeJ GdoefGLGJ GdeHGQc s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B295s
(3eUOQ GbJfGA GdCUd (B:s
(3GdecJHI GdCgdjI HHGQjS (B(5988) s
Keywords: (3GdJUha hGdBOGH GdTQYjIs